INFORMASI OBAT CAIR UNTUK ANAK MENGGUNAKAN AUGMENTED REALITY BERBASIS ANDROID - Wafiah, Andi (Jurnal Sintaks Logika, 2021)
The purpose of this research is to know the Android liguid drug information for children using Augmented Riality base. In ApotikAbidfarmaparepare. This research showed that image processing methadthay applied by vuforia using this Aplication allowed for user to see liguid drug information in ApotikAbidFarmaparepare just shine the camera which provided to marker then push the information menu, composition, and indication in that marker. Acoording to this explanation abtained the research result like the limition form image processing used, where from pour samples to do, all of the test has cortion detection limits in minimal rang e 20 cm, and maximum range variesbetwen 30 cm – 35 cm, Because many factors like3 the things guality which detected and low shining factor. Beside that, also abtained results that the best degree for showing optimal resuit in 90 or the camera position in front of the object. Moreover, the level of user satisfuction showing positive respond to words use of the create application.